A Proposed Strategy to Enable Community Service through Technological Innovation - Heba Tawfiqe Abu Eyadah; Anas Odibat (Universitas Negeri Malang, 2025)
This study addresses the critical challenge of technological disparities that hinder effective community service delivery in underserved regions. The research emphasizes the urgency of leveraging technological innovation to enhance social equity and community empowerment. A mixed-methods approach was employed, combining quantitative surveys to assess digital access levels with qualitative case studies of successful technology-driven community service models. The proposed strategy is built on four foundational pillars: comprehensive digital infrastructure development, inclusive capacity-building programs, community-oriented innovation frameworks, and sustainable multi-stakeholder partnerships. Key findings demonstrate that integrated technological solutions significantly improve the scalability, efficiency, and impact of community services. Implementation of pilot projects revealed a 40% increase in service accessibility and a 30% reduction in operational costs. The study concludes that a systematically designed technology-enabled strategy can transform community service delivery, fostering sustainable development and digital inclusion. The results provide a replicable framework for policymakers and organizations seeking to harness innovation for social good.